Компаративна анализа на платната инфраструктура во Европската Унија и платната инфраструктура на Република Македонија - Мирчески, Тони (Економски факултет, УКИМ, Скопје, 2017)
From the perspective of central banks and other relevant authorities, payment infrastructure, such as payment systems, securities settlement systems, clearing systems and central counterparties, represent dynamic objects that are in a constant process of evolution and that process will pursue in the future. The complexity of the payment infrastructure where payments and financial instruments are processed, does not arise only from the high number and value, but also from the plethora of financial innovations. A key challenge for central banks and other relevant authorities is the development of a modern, stable and efficient payment infrastructure that will be in function of the national and global economy, thus ensuring development of safe and efficient financial markets. The global economic crisis proved the need of revision of international standards for payment infrastructure, as well as the responsibilities of central banks and other relevant authorities. Therefore, globally, both the implementation of new standards and the responsibilities of the authorities have become a big challenge. By accepting this challenge, the research in doctoral dissertation is primarily focused on the systematic approach to setting of the theoretical concepts of payment infrastructure, by always keeping in mind the strategic approach of the Republic of Macedonia for EU integration. For that purpose, a cross-section of the dynamic state of the payment infrastructure in the EU and the process of its integration is presented. The establishment of a standard review of the Macedonian payment infrastructure and its development is a solid basis for application of comparative statistical and descriptive approach, which is a good tool for setting concepts and strategic approach of the development of the national payment infrastructure and defining the responsibilities of the National Bank of the Republic of Macedonia and the Securities and Exchange Commission of the Republic of Macedonia.
Comparative analysis of payment infrastructure in the European Union and payment infrastructure of the Republic of Macedonia
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубе Трпески.
Keywords: payment systems, payments, payment infrastructure, payment instruments, securities settlement systems, trading, clearing and settlement